Piroxicam induced submassive necrosis of the liver. Issue 10 (October 1992) - Paterson, D; Kerlin, P; Walker, N; Lynch, S; Strong, R
Abstract : Several widely used non-steroidal anti-inflammatory drugs have been reported as causing severe hepatitis. Three cases of severe acute hepatitis have been reported in association with piroxicam. A fatal submassive necrosis that occurred in a 68 year old lady who had received piroxicam for 15 months is described. A 48 year old man who developed submassive hepatic necrosis six weeks after beginning piroxicam but was successfully treated with orthotopic liver transplantation is also reported. Piroxicam may induce submassive necrosis of the liver, probably as an idiosyncratic reaction.